Design and implementation of a Targeted HealthcaRe InnoVation & Entrepreneurship (THRIVE) fellowship program - Ian C. Odland; Joseph Borrello; Layla Fattah; Tyree D. Williams; Kevin D. Costa; David Putrino; Brian Nickerson; Holly Oemke; Turner Baker; James McKay; Dov B. Shamir; Juan Quijano; et al. (PLoS ONE, 2025)
The Targeted HealthcaRe InnoVation & Entrepreneurship (THRIVE) Fellowship was created to bridge the gap between healthcare professionals, who often lack experience in technology development and entrepreneurship, and engineers or technology experts, who may not fully understand clinical needs. This eight-month extracurricular program introduces medical and graduate students to the process of health technology innovation. Fellows form multidisciplinary teams to identify and address an unmet clinical need, following Biodesign principles. The program consists of three phases: (1) introduction to healthcare innovation and foundational skills; (2) team formation, mentor selection, and customer discovery; and (3) solution prototyping, pitching, and business plan development. A retrospective analysis of the 2022–2023 cohort evaluated participant demographics, subjective outcomes (Likert-scale surveys on skill acquisition and program satisfaction), and objective metrics (e.g., milestones completed, funds raised, technology disclosures). Descriptive statistics and paired t-tests for pre-post comparisons were used in the analysis. Of the 56 applicants, 29 were accepted, and 20 completed the program. Fellows rated overall satisfaction at 4.45/5, with 85% planning to incorporate healthcare innovation into their future careers. On average, teams met 10.4 of 12 milestones, raised $10,250 in additional funds (in addition to the $5,000 fellowship grant), and filed multiple technology disclosures. Fellows reported significant gains in key innovation skills (p = 1.3E-5) and spent an average of 7.4 hours per week on their projects. The THRIVE Fellowship fosters interdisciplinary collaboration, practical skill development, and a heightened commitment to healthcare innovation. Early successes include strong participant satisfaction, measurable skill acquisition, and substantial external funding. Future program refinements will focus on expanded mentor engagement, enhanced skill-building resources, and long-term tracking of career outcomes. This model may serve as a scalable approach to training future clinicians and researchers in healthcare technology innovation.